Nutrition and hydration management among stroke patients in inpatient rehabilitation: a best practice implementation project. Issue 1 (18th March 2021) - Mullins, Natalie
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Introduction: In 2012 in Australia, stroke was the cause of 11 791 deaths and affected the lives of over 420 000 survivors. Survivors experience significant physical and cognitive deficits; and accumulate a 43% risk of subsequent stroke. Effective evidence-based management of stroke is essential. The Stroke Foundation released Clinical Guidelines for Stroke Management in 2017. Within these guidelines, nutrition and hydration are recognized as important aspects of poststroke management. Audit criteria drawn from the guidelines focussed on the role of multidisciplinary screening, assessment, monitoring and treatment of dehydration and malnutrition; as well as provision of nutrition education and counselling relating to secondary prevention of stroke. The implementation team included dietetics, medical and nursing staff. The project was completed in the stroke unit at Hampstead Rehabilitation Centre (Adelaide, South Australia). Objectives: To determine current compliance with Australian Clinical Guidelines of Stroke Management 2017, specifically those relating to nutrition, hydration and secondary prevention. To engage a multidisciplinary team to develop and implement strategies promoting best practice care for stroke survivors. Methods: The project utilized the Joanna Briggs Institute Practical Application of Clinical Evidence System audit tool for baseline and follow-up audit, and the Getting Research into Practice feedback tool to facilitate practice change. Results: Postimplementation audit results demonstrated improvement in four criteria: Criterion 3 – Nondysphagic stroke patients with confirmed malnutrition or at risk for malnutrition are offered oral nutrition supplements, Criterion 4 – Stroke patients who are malnourished or at risk of malnutrition are referred to a Dietitian for individualized medical nutrition therapy, Criterion 5 – The hydration status of stroke patients is assessed, monitored and managed throughout their hospital admission, Criterion 6 – Stroke survivors are referred to a Dietitian for the provision of individualized dietary advice which incorporates secondary prevention strategies. Criterion 7 (A collaborative goal setting approach which includes the stroke survivor, their families and carers and the rehabilitation care team is implemented) remained consistent at 100% compliance. Although Criteria 5 and 6 improved during the project, they remained below 75% compliance therefore, offer ongoing opportunity for development. Criterion 1 (Stroke patients are screened for malnutrition upon admission using a validated malnutrition screening tool) and Criterion 2 (Stroke patients are rescreened for malnutrition weekly using a validated malnutrition screening tool) were affected by a change from written to electronic medical records therefore, the results did not accurately reflect the intervention. Conclusion: The current project successfully increased knowledge of nutrition and hydration management for stroke survivors and more closely aligned inpatient management with best practice guidelines to improve health outcomes. It highlighted areas of focus moving forward and has prompted ongoing work for sustaining evidence-based practice change.